1984
DOI: 10.1891/0047-2220.15.1.40
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Employer Attitudes Toward The Worker Problems of Eight Types of Disabled Workers

Abstract: Employer attitudes toward the work traits of eight types of disabled workers were variable. There were significant differences on attitudes toward the specific groups of disabled on eleven of the twelve work traits. The blind and mentally retarded would encounter the greatest employer discrimination while more favorable attitudes were shown toward hiring epileptics and amputees. Across all types of disabilities, the greatest concerns were lower work productivity, higher accident and workman compensation rates.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 0 publications
2
39
0
Order By: Relevance
“…However, the fact that small-sized self-employed businesses as the typical pattern of enterprise in Greece, allows us a degree of generalization. A series of investigations of the effects of the type of disability on employers' attitudes have produced similar results; employers express greater concerns about employing people with mental disabilities than employing those with physical disabilities (Fuqua, Rathburn & Gade 1984, McFarlin, Song & Sonntag 1991, Jones et al 1991, Callahan 1994, Scheid 1999. In a more recent study, Gilbride et al (2000), by demonstrating the Employer Hiring Practices and Perceptions Survey to 200 employers, found that it would be easier to employ people with a cancer diagnosis, heart impairment or living with HIV than it would be to employ people with a moderate or severe learning disability or blindness.…”
Section: Discussionmentioning
confidence: 87%
“…However, the fact that small-sized self-employed businesses as the typical pattern of enterprise in Greece, allows us a degree of generalization. A series of investigations of the effects of the type of disability on employers' attitudes have produced similar results; employers express greater concerns about employing people with mental disabilities than employing those with physical disabilities (Fuqua, Rathburn & Gade 1984, McFarlin, Song & Sonntag 1991, Jones et al 1991, Callahan 1994, Scheid 1999. In a more recent study, Gilbride et al (2000), by demonstrating the Employer Hiring Practices and Perceptions Survey to 200 employers, found that it would be easier to employ people with a cancer diagnosis, heart impairment or living with HIV than it would be to employ people with a moderate or severe learning disability or blindness.…”
Section: Discussionmentioning
confidence: 87%
“…In particular, mental illness, broadly defined, showed a stronger negative association with employment outcomes for both male and female workers with disabilities (Baldwin & Johnson, 1994;Baldwin, Zeager, & Flacco, 1994;Gaebel & Baumann, 2003;Jones, 2008Jones, , 2011. 2 Other types of disabilities, including respiratory ailments, heart problems, and musculoskeletal conditions, were still negatively associated with employment outcomes, but to a lesser extent (Bartel & Taubman, 1986;Fuqua, Rathburn, & Gade, 1984;Zwerling et al, 2002). Indeed, studies have shown that individuals with cognitive disabilities are almost always the most disadvantaged (Hum & Simpson, 1996;Jones, 2008;Wilkins, 2004).…”
Section: Disability Typementioning
confidence: 99%
“…However, concerns about job performance and absenteeism may also motivate employers. Stereotypes of disabled employees, including perceptions of lower productivity and higher accident and turnover rates, may affect hiring rates (Fuqua et al 1984;Greenwood and Johnson 1987;Lester and Caudill 1987). In contrast, previous research shows that employers are generally satisfied with the performance of workers with disabilities (McFarlin et al 1991), and that these individuals frequently demonstrate levels of performance, absenteeism, accidents, and turnover equal to or better than the general workforce (Braddock and Bachelder 1994;Mackay 1995;Unger 2001).…”
Section: Introductionmentioning
confidence: 99%